Pengaruh Komunikasi Pimpinan dan Pengawasan Kerja Terhadap Kinerja Karyawan Pada PT. Pegadaian Syariah (Persero) UPS Batoh Banda Aceh - Salsabila Rukmayana; Suryani Murad; Sulfitra (Yayasan Madinah Al-Aziziyah, 2026)
Study This aims to determine the influence of leadership communication and work supervision on employee performance at PT. Pegadaian Sharia Banda Aceh Branch. The method used is an associative method that aims to determine the influence or relationship between two or more variables. The determination of the research sample uses a saturated sample technique . The sample used in this study was 40 employees at PT. Pegadaian Sharia Banda Aceh Branch and willing to be respondents. The analysis method applied is multiple linear regression analysis. The results of the study indicate that leadership communication has a partial positive and significant effect on employee performance at PT. Pegadaian Sharia Banda Aceh Branch Partial work supervision has a positive and significant effect on employee performance at PT. Pegadaian Sharia Banda Aceh Branch. Leadership communication and work supervision simultaneously have a positive and significant effect on employee performance at PT. Pegadaian Sharia Banda Aceh Branch . Employee performance improvement is determined by leadership communication and work supervision. The better the leadership communication and the better the work supervision carried out, the greater the opportunity for PT. Pegadaian Sharia Banda Aceh Branch in improving employee performance.